KINERJA PEMERINTAH DESA DALAM PENERAPAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA MPANAU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Harmain, Moh. Fadli Sumarwanto; Pasindringi, Andi; Kurnia, Intam (Katalogis, 2019)
Based on the results of the discussion that the Performance of the Village Government in Implementing the Village Financial System Application (SISKEUDES) in Mpanau Village, Sigi Biromaru District, Sigi Regency. Basically has not been in line with the community's expectations. This can be seen from 2 indicators, Service Quality and Accountability Mpanau Village Government Sigi Biromaru District Sigi Regency has not run optimally in the application of Siskeudes application due to limited human resources who understand the Siskeudes application, lack of training and Bimtek regarding Siskeudes application to staff / employees other villages, and lack of discipline and responsibility at work. While the other 3 indicators are good, it can be seen from Productivity, Programs and activities and services that have been running effectively, efficiently, and transparently in working for the management of village fund allocations and village funds inputted into the Siskeudes application. Responsiveness, the ability of the Mpanau village government in responding quickly to the wishes and needs of the community in Mpanau and Responsibility Villages, the Mpanau Village Government in carrying out its duties and functions are based on good and proper administration in providing public services.